Sterile Pyuria in Kawasaki Disease: A Large Prospective Cohort Study - Liu, Xiaoliang; Wang, Lin; Shao, Shuran; Zhang, Nanjun; Wu, Mei; Liu, Lei; Hua, Yimin; Zhou, Kaiyu; Yu, Li; Wang, Hua; Wang, Chuan (Frontiers in Cardiovascular Medicine, 2022)
Background: Kawasaki disease (KD) is an acute systemic vasculitis and is becoming the leading cause of acquired cardiac disease in Children. Sterile pyuria is a known complication of KD. However, its associations with the inflammatory reaction severity, IVIG resistance as well as coronary artery lesions (CALs) in KD remain elusive. Aims: We aimed to analyze the clinical profiles of sterile pyuria in KD, to determine whether sterile pyuria is an indicator of the disease severity in patients with KD, and to assess the associations between sterile pyuria and IVIG resistance as well as CALs. Methods: We prospectively collected data from 702 patients with KD between January 2015 and June 2020. Profiles of patients with sterile pyuria (group A, n=63) were compared to those of patients without sterile pyuria (group B, n=639). The associations between sterile pyuria and IVIG resistance as well as CALs in KD were further determined by univariate and/or multivariate logistic regression analysis. Results: Sterile pyuria was observed in 9.0% of patients with KD, without predominance in age spectrum and gender. The levels of neutrophil percentages, alanine transaminase, total bilirubin, blood urea nitrogen, creatinine, the incidence of initial IVIG resistance, and rate of moderate/giant coronary artery aneurysms (CAAs) were significantly higher in group A than that in group B. Sterile pyuria was identified as an independent risk factor for initial IVIG resistance, yielding high specificity (92.7%) and low sensitivity (18.5%). However, sterile pyuria was not associated with repeated IVIG resistance and persistence of CALs in KD. Conclusion: The incidence of sterile pyuria is relatively low in KD patients. Patients with sterile pyuria in KD exhibited a more severe inflammatory burden and were more likely to develop the initial IVIG resistance and moderate/giant CAAs. The overall prognosis of KD patients with sterile pyuria was satisfactory.